PACE trial claims of recovery are not justified by the data: a rejoinder to Sharpe, Chalder, Johnson, Goldsmith and White (2017). Issue 1 (2nd January 2017) - Wilshire, Carolyn; Kindlon, Tom; McGrath, Simon
ABSTRACT: Background: Recently, we critically evaluated the claim from the PACE trial that cognitive behavioural therapy (CBT) and graded exercise therapy (GET) can lead to recovery from chronic fatigue syndrome (CFS). We showed that the trial's definition of recovery was so loose it failed to capture the term's core meaning. Also, this definition was substantially loosened very late in the trial, in ways that favoured the study hypotheses. The investigators do not acknowledge any of these criticisms and stand by their original analyses. Purpose: To examine the arguments advanced in defence of PACE's recovery claims. Methods: Drawing on various sources of evidence, we consider three major arguments raised in defence of PACE's recovery claims: (1) that since there is no agreed definition of recovery, it comes down to a matter of opinion; (2) that the original definition was 'too stringent'; and (3) the revised definition generates results that align with previous studies. Results: We find that: (1) 'recovery' is a strong claim, which implies evidence a return to health, and that the trial's final definition did not preserve this core meaning; (2) there is no evidence to suggest that the original protocol-specified definition was 'too stringent'; (3) absolute recovery rates from other studies are not a legitimate source of support for the recovery definition used. Conclusions: The PACE trial provides no evidence that CBT and GET can lead to recovery from CFS. The recovery claims made in the PACE trial are therefore misleading for patients and clinicians.